2017
DOI: 10.1371/journal.pbio.2000374
|View full text |Cite|
|
Sign up to set email alerts
|

The mechanism of sirtuin 2–mediated exacerbation of alpha-synuclein toxicity in models of Parkinson disease

Abstract: Sirtuin genes have been associated with aging and are known to affect multiple cellular pathways. Sirtuin 2 was previously shown to modulate proteotoxicity associated with age-associated neurodegenerative disorders such as Alzheimer and Parkinson disease (PD). However, the precise molecular mechanisms involved remain unclear. Here, we provide mechanistic insight into the interplay between sirtuin 2 and α-synuclein, the major component of the pathognomonic protein inclusions in PD and other synucleinopathies. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 48 publications
2
141
0
2
Order By: Relevance
“…In addition to N‐terminal acetylation, lysine residues can also undergo acetylation. Mass spectrometry analysis of endogenous AS from mice revealed that Lys6 and Lys10 can be acetylated and that acetylation reduces its aggregation in vitro and reduces toxicity in vivo (de Oliveira et al ).…”
Section: Post‐translational Modifications Of α‐Synucleinmentioning
confidence: 99%
“…In addition to N‐terminal acetylation, lysine residues can also undergo acetylation. Mass spectrometry analysis of endogenous AS from mice revealed that Lys6 and Lys10 can be acetylated and that acetylation reduces its aggregation in vitro and reduces toxicity in vivo (de Oliveira et al ).…”
Section: Post‐translational Modifications Of α‐Synucleinmentioning
confidence: 99%
“…It has been confirmed that selective inhibitors of SIRT2 can protect against α-syn-mediated toxicity and dopaminergic cell death, both in vitro and in a Drosophila model of PD [19]. Notably, a recent study showed that α-syn can be deacetylated by SIRT2, and α-syn acetylation is a key regulatory mechanism governing aggregation and toxicity, demonstrating the potential therapeutic value of SIRT2 inhibition in synucleinopathies [21]. The present study confirmed that mimics of miR-486-3p, which acts as an inhibitor of SIRT2, could reduce the aggregation state of LBs and α-syn-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study showed that SIRT2 governs α-syn aggregation [21]. To confirm whether miR-486-3p regulates α-syn aggregation through SIRT2, we established a α-syn aggregation model in both SH-SY5Y and U87 cells, involving the co-expression of a C-terminally modified form of α-syn with an increased propensity for aggregation and synphilin-1 (an α-syn interactor that potentiates its aggregation) in neural cells [3].…”
Section: Mir-486-3p Reduces α-Syn Inclusions and Suppresses α-Syn Toxmentioning
confidence: 99%
See 1 more Smart Citation
“…The explosion in the field of proteostasis in the 2000s, brought about an important knowledge on how cells and organisms handle aSyn, attempting to refold or recycle the protein into its basic components (Cuervo et al ; Bandyopadhyay and Cuervo ). More recently, technological developments in biochemical, biophysical, proteomic, and imaging approaches, provided insight into the structure, chemical modifications (posttranslational modifications, PTMs), and subcellular distribution of aSyn (Mostofi et al ; Goncalves and Outeiro ; de Oliveira et al ; Pinho et al ). Phosphorylation, for example, is widely used as a marker for pathological aSyn (Fujiwara et al ; Paleologou et al ), but other PTMs are emerging as additional studies are performed.…”
mentioning
confidence: 99%